Expected impacts of increases in international prices of fertilizer in Rwanda: Estimates from a microsimulation - Spielman, David J.; Mugabo, Serge; Rosenbach, Gracie; Ndikumana, Sosthene; Benimana, Gilberthe Uwera; Ingabire, Chantal (International Food Policy Research Institute, 2022)
International fertilizer prices have increased rapidly since 2020 due to multiple factors. This note assesses the impact of these price increases on Rwanda’s agriculture sector, with an emphasis on implications for crop production, subsidy costs, and the Government of Rwanda’s agricultural budget. Using data from the Seasonal Agricultural Surveys, we simulate the impact of increasing fertilizer prices on fertilizer demand and use, which in turn affects fertilizer value-cost ratios at the plot level and, ultimately, maize, rice, and Irish potato output and the Government’s fertilizer subsidy bill. Findings indicate the following • At current subsidy rates and market prices, national output across all seasons could decrease by up to 3 percent for maize, 2 percent for rice, and 12 percent for Irish potato under strong assumptions about farmers’ sensitivity to fertilizer prices. Weaker assumptions about their sensitivity result in much smaller decreases in output. • At current subsidy rates and market prices, the fertilizer subsidy bill may increase from 7 percent of MINAGRI’s budget—inclusive of funds earmarked for districts—to 12 percent. Ultimately, the policy challenge will be to determine whether a return to the original subsidy levels and rates is feasible and under what conditions. In the short term, volatility in international fertilizer prices may continue, particularly in light of the conflict in Ukraine, making it necessary to maintain the current subsidy regime. But I the medium term, it is possible to move towards market prices for fertilizer without dramatically affecting output, thereby providing more fiscal space for other priorities.